On the 3rd order linear differential equation - Moreno-Ley, BL; Lopez-Bonilla, J; Tuladhar, B Man (Kathmandu University Journal of Science, Engineering and Technology, 2013)
If for an arbitrary 3th order linear differential equation, non-homogeneous, we know two solutions of its associated homogeneous equation (HE), then we show how to determine the third solution of HE and the particular solution of the original equation. Kathmandu University Journal of Science, Engineering and Technology Vol. 8, No. II, December, 2012, 7-10 DOI: http://dx.doi.org/10.3126/kuset.v8i2.7319